Investigation and modelling of the turbulent wall pressure fluctuations on the bulbous bow of a ship. (November 2016) - Magionesi, Francesca; Di Mascio, Andrea
Abstract: For the effective operation of sonar systems mounted inside the bulb of fast ships, it is important to reduce all the possible noise and vibration sources that radiate noise and interfere with sonar sensor response. In particular, pressure fluctuations induced by turbulent boundary layers on the sonar dome surface represent the major source of self-noise for on-board sensors. Reliable calculations of structural vibrations and noise radiated inside the dome require valid statistical descriptions of wall pressure fluctuations beneath the turbulent boundary layer. Previous research about wall pressure fluctuations deals with equilibrium turbulent boundary layers on flat plates in zero pressure gradient flow, for which scaling laws for power spectral densities and empirical models for the cross spectral densities are well established. On the contrary, turbulent boundary layers on bulbous bow exhibit the combined effects of three-dimensionality, streamline and spanwise curvatures and pressure gradients. In order to collect information about realistic configurations, wall pressure fluctuations were measured in an experimental campaign performed in a towing tank; data were collected at two different locations along a large scale model of a ship bulb and their spectral characteristics were investigated in terms of auto and cross spectral densities. Mean flow parameters of the boundary layer, required in the analysis, were obtained by a finite volume code that solves the Reynolds Averaged Navier Stokes Equations. The applicability of classical scaling laws for pressure spectra on zero pressure gradient flat plate was investigated, together with the spatial characterization of the wall pressure fluctuations in the space-frequency domain; parameters of some semi-empirical models available in the scientific literature were tuned to fit the measured pressure field.